Les populations insulaires face au changement climatique : des migrations a anticiper - Christel Cournil; François Gemenne (VertigO)
Impacts of climate change on island countries have been made clear in the assessment reports of the IPCC. Though the first consequences will be environmental, with sea-level rise and the increase of extreme weather events, socio-economic consequences will quickly follow. In the next twenty years, due to sea-level rise and soil salinisation, the living conditions of islanders will quickly deteriorate. Small island states, gathered within the AOSIS, have voiced strong and clear concerns at the Copenhagen Conference, demanding that the goal for maximum temperature rise be set at 1.5°C instead of 2.0°C. In support of their revendications, small island states often mention the issue of 'climate refugees', who have become the faces of climate change in the last few years. Beyond its symbolic impact, the issue of 'climate refugees' raises several political challenges, which are especially salient in the context of small island states. The forecasted disappearing of some nations also raises legal questions about the protection of future refugees, but also about a new form of statelessness related to the legal and political continuity of a state, even though its territory might vanish.